2003: In the future …: Refereed Proceedings of the 2003 Biannual Language and Academic Skills in Higher Education Conference: “In the future …”, Flinders University, 24-25 November 2003 - Deller-Evans (Editor), Kate; Zeegers (Editor), Peter (Journal of Academic Language and Learning, 2026)
Formatting note: In the pdf, an article can be accessed directly by clicking on its title in the table of contents or via the Bookmarks pane. Introduction KEYNOTE ADDRESSES Challenges of internationalisation: Enhancing intercultural competence and skills for critical reflection on the situated and non-neutral nature of knowledge: Simone Volet … 1 What students know about making good use of learning and teaching situations: Michael Lawson … 11 Where do we come from? What are we? Where are we going? Peter Zeegers … 25 REFEREED PAPERS The Language and Academic Skills Advisor in the teaching partnership: What should be our role? Janice Catterall … 37 Academic and/or general? How the classification of LAS Advisers affects us and our institutions: Kate Chanock, Julianne East & Judy Maxwell … 43 Coming of Age: Developing a genealogy of knowledge in the LAS field: Alisa Percy & Jeannette Stirling … 53 Meeting the challenges of learning support for on-campus, off-campus and off-shore students in a multi-campus university: Bev Kokkinn & Marie Stevenson … 63 Advising for engagement - how do WE engage? Ros Martins … 71 Student perceptions of preparedness for first-year university assignment writing: The discipline of Marketing: Rosemary Clerehan & Ian Walker … 79 To Stay Or Not To Stay: Factors affecting international and indigenous students’ decisions to persist with university study and the implications for support services: Salah Kutieleh, Sandra Egege & Douglas Morgan … 89 The faculty mentor program: An initiative to support the transition to university f or on-campus students at a regional university: Robyn Muldoon … 99 Draw-Talk-Write: Russell Gluck, Kim Draisma, John Fulcher & Marion Worthy … 109 From Literature to Literacy: some reflections on my personal journey and some thoughts for the future: Neera Handa … 117 From integration to transformation: Bronwyn James, Jan Skillen, Alisa Percy, Holly Tootell & Helen Irvine … 127 Evaluating evaluations: A case study in peer mentoring: Erst Carmichael … 139 The challenge of developing engaging interactive tertiary online language materials based on instructional design and learning principles: Khoo Cheng-Choo … 149 Study skills and the math-anxious: Reflecting on effective academic support in challenging times: Christopher Klinger … 161